A Comparative Study of Apical Microleakage Using the Conventional Lateral Condensation and Mechanical Lateral Condensation Techniques - Shahriari, Shahriar; Jalalzadeh, Seyed Mohsen; Abedi, Hasan; Abedi, Hasan (Iranian Endodontic Journal, 2008)
INTRODUCTION: This study compared apical dye penetration using lateral condensation technique (LC) and LC technique with a reciprocal handpiece (mechanical lateral condensation or MLC) as a new method. MATERIALS AND METHODS: Forty-eight human extracted straight canine teeth were used. After crown amputation, the teeth were randomly divided into four experimental groups of 10 teeth each and two negative and positive control groups of 4 teeth each. The groups were as follows: IA, 10 obturations completed by operator A using the LC technique; Group IB, 10 obturations completed by operator B using the LC technique; Group IIA, 10 obturations completed by operator A using the MLC technique; and Group IIB, 10 obturations completed by operator B using the MLC technique. All roots were placed in 2% methylene blue dye and centrifuged at 3000 rpm for 3 minutes. Following centrifugation, the roots were cut along their long axis and evaluated under a stereomicroscope to measure the depth of dye penetration. RESULTS: A t-test showed that the teeth which were filled by the MLC technique had less dye penetration in comparison with LC technique (P<0.05). CONCLUSION: This in vitro study illustrates that canals obturated with the MLC technique had superior apical seal than canals filled with the LC technique.